2017
DOI: 10.1016/j.canep.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in colorectal cancer survival at a safety net hospital

Abstract: Background While racial disparity in colorectal cancer survival have previously been studied, whether this disparity exists in patients with metastatic colorectal cancer receiving care at safety net hospitals (and therefore of similar socioeconomic status) is poorly understood. Methods We examined racial differences in survival in a cohort of patients with stage IV colorectal cancer treated at the largest safety net hospital in the New England region, which serves a population with a majority (65%) of non-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…A meta-analysis [40] revealed that mucinous tumors were 50% more common in the proximal compared with distal colorectum [40]. Our results are in line with other studies suggesting a higher prevalence of mucinous containing tumors in younger age patients [23,24]. In our cohort, mucinous histology tumors were more common in younger AAs versus CAs (i.e., 18 vs 7%), whereas in older patients, we observed the opposite pattern (5 vs 8%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A meta-analysis [40] revealed that mucinous tumors were 50% more common in the proximal compared with distal colorectum [40]. Our results are in line with other studies suggesting a higher prevalence of mucinous containing tumors in younger age patients [23,24]. In our cohort, mucinous histology tumors were more common in younger AAs versus CAs (i.e., 18 vs 7%), whereas in older patients, we observed the opposite pattern (5 vs 8%).…”
Section: Discussionsupporting
confidence: 89%
“…Notable differences by race and age in the prevalence of poor prognostic clinicopathologic features in CRCs have been reported [7,[17][18][19][20]. For example, younger AAs often present with a higher stage of disease and more proximal colon cancers (than rectal) compared with younger CAs [7,18], which are associated with poorer prognosis [21,22] Also, mucinous and signet cell histology CRCs are more common in younger age patients [23], including a few reports showing a higher prevalence in younger AAs compared with CAs [17,24]. Mucin containing CRCs occur more frequently in the proximal colon than the rectum and also have poorer prognosis [25,26].…”
mentioning
confidence: 99%
“…Several studies found an association of race on CRC survival. 22,23 Our recent work showed that black patients with mCRC at Boston Medical Center had a significantly lower survival compared with white patients. 23 Therefore, we examined whether the association of c-Cbl expression and survival differed according to race.…”
Section: C-cbl Expression Correlates With the Overall Survival Of Patmentioning
confidence: 99%
“…22,23 Our recent work showed that black patients with mCRC at Boston Medical Center had a significantly lower survival compared with white patients. 23 Therefore, we examined whether the association of c-Cbl expression and survival differed according to race. Among black patients with mCRC, those with low and high c-Cbl expression (divided based on median normalized c-Cbl expression) had a median overall survival of 2.1 and 3.8 years, respectively (P Z 0.0284).…”
Section: C-cbl Expression Correlates With the Overall Survival Of Patmentioning
confidence: 99%
“…It has a greater economic impact from premature death and disability than all causes of death combined worldwide [2]. It is well known that different racial groups have significantly different incidence and mortality rates for certain cancers [3][4][5][6][7][8][9]. For all cancer types combined, the incidence rates in the United States are 465.3, 463.9, and 291.7 per 100 000 people, for non-Hispanic white (NHW), non-Hispanic black (NHB), and Asian/Pacific Islander (API) populations, respectively [1].…”
Section: Introductionmentioning
confidence: 99%